Simulation of steady state operation of induction motor / Mohd Adam Abdullah - Abdullah, Mohd Adam (2001)
This thesis describes developed software to perform the steady state simulation on induction motors. The software is developed using Microsoft Visual Basic (VB) Version 6.0. The results of the simulation using the developed software will provide the performance data of the induction motor and the graph of torque versus slip, efficiency versus slip and line current versus slip. The result of the simulation also provides the effect of changing the rotor resistance and the effect of changing input voltage on the motor performance.